OCULAR HYPERTENSION AFTER INTRAVITREAL INJECTION OF 2-MG TRIAMCINOLONE. Issue 1 (January 2020) - Storey, Philip P.; Obeid, Anthony; Pancholy, Maitri; Goodman, Jake; Borkar, Durga; Su, Daniel; Regillo, Carl
Abstract : Purpose: To report the incidence and course of ocular hypertension after intravitreal injection of 2-mg triamcinolone acetonide (IVT). Methods: In a retrospective, consecutive series, all patients receiving 2-mg IVT at a single institution between March 1, 2012, and March 1, 2017, with a minimum of 3-month follow-up were reviewed. Ocular hypertension was defined as an intraocular pressure (IOP) measurement over 24 mmHg at any follow-up visit after IVT. Patients receiving topical, periocular, or intravitreal corticosteroid other than 2-mg IVT were excluded. Results: A total of 106 eyes in 100 patients receiving at least one injection of 2-mg IVT were included. Eyes received an average of 2.9 injections (range 1–17), and average patient follow-up was 15.1 months (range 3.0–52.5 months). A total of 14 eyes (13.2%) in 14 patients developed ocular hypertension after a median of 1.5 injections (range 1–9) with an average peak IOP of 29 mmHg (range 25–38 mmHg). Overall, a total of 11 eyes (10.4%) had an IOP elevation ≥10 mmHg above baseline at any point after first IVT. In all cases of ocular hypertension, IOP was successfully managed with observation or topical IOP-lowering medication alone; no patients required surgical intervention. Conclusion: Ocular hypertension developed in 13.2% of eyes receiving intravitreal injection of 2-mg triamcinolone acetonide. Incidence of ocular hypertension after 2-mg IVT compares favorably with other intravitreally administered corticosteroids. Abstract : In 106 eyes receiving 2-mg intravitreal triamcinolone, 13.2% of eyes developed intraocular pressure greater than 24 mmHg at any follow-up visit. Ocular hypertension incidence after 2-mg intravitreal triamcinolone compares favorably with other intravitreal steroid agents.